PITTORESKE PROSPEKTER: Landskab ifølge gentlemen anno 1800 - Jørgensen, Kirsten (Tidsskriftet Antropologi, 1997)
Kirsten Jørgensen: Picturesque Prospects. Landscape According to Gentlemen Anno 1800 The idea of picturesque landscape, which emerged in Britain in the 18th century and reached its peak of popularity in the decades around 1800, is based on an appropriation of wildemess to the norms of landscape art. The highly valued picturesque prospects were those which especially reminded the viewer of Italian landscape paintings from the 17th century. The present article addresses itself to the question of how on earth the British traveller was able to enframe a picturesque prospect in open air, surrounded as he was by multiple, unframed motifs. The idea of the picturesque landscape is first approached through an analysis of the two other contemporary categories of landscape, analytically designated as the monotonous and the cultivated landscape, to which the picturesque cognitively is defined and to which it is enframed in opposition. Second, the idea of the picturesque landscape is itself analysed. It is argued that rather than any inherent properties of the viewed country being decisive in the definition of the picturesque landscape, it is the gaze of the viewer, the picturesque eye as a contemporary calls it, and the cultivated mind of the viewer which make the appropriation of wild nature to the norms of art possible.and thus it is the travelling gentleman who evokes the picturesque prospect and calls into being.